Diagnostic accuracy of a prototype point-of-care test for ocular Chlamydia trachomatis under field conditions in The Gambia and Senegal. - Emma M Harding-Esch; Martin J Holland; Jean-François Schémann; Sandra Molina; Isatou Sarr; Aura A Andreasen; Chrissy h Roberts; Ansumana Sillah; Boubacar Sarr; Edward F Harding; Tansy Edwards; Robin L Bailey; et al. (Public Library of Science (PLoS), 2011)
The clinical signs of active trachoma are often present in the absence of ocular Chlamydia trachomatis infection in low prevalence and mass treated settings. Treatment decisions are currently based on the prevalence of clinical signs, and this may result in the unnecessary distribution of mass antibiotic treatment. We aimed to evaluate the diagnostic accuracy of a prototype point-of-care (POC) test, developed for field diagnosis of ocular C. trachomatis, in low prevalence settings of The Gambia and Senegal.Three studies were conducted, two in The Gambia and one in Senegal. Children under the age of 10 years were screened for the clinical signs of trachoma. Two ocular swabs were taken from the right eye. The first swab was tested by the POC test in the field and the result independently graded by two readers. The second swab was tested for the presence of C. trachomatis by Amplicor Polymerase Chain Reaction. In Senegal, measurements of humidity and temperature in the field were taken. A total of 3734 children were screened, 950 in the first and 1171 in the second Gambian study, and 1613 in Senegal. The sensitivity of the prototype POC test ranged between 33.3-67.9%, the specificity between 92.4-99.0%, the positive predictive value between 4.3-21.0%, and the negative predictive value between 98.0-99.8%. The rate of false-positives increased markedly at temperatures above 31.4°C and relative humidities below 11.4%.In its present format, this prototype POC test is not suitable for field diagnosis of ocular C. trachomatis as its specificity decreases in hot and dry conditions: the environment in which trachoma is predominantly found. In the absence of a suitable test for infection, trachoma diagnosis remains dependent on clinical signs. Under current WHO recommendations, this is likely resulting in the continued mass treatment of non-infected communities.